Respuesta :
Let
Given statement be P(n)
[tex]\\ \sf\longmapsto P(n)=2n^3-3n^2+n+6,is\:a\:multiple\:of\:6[/tex]
For n=1
[tex]\\ \sf\longmapsto P(1)=2(1)^3-3(1)^2+1+6=2-3+7=-1+7=6[/tex]
- For n=1 P(n) is true
Now
P(k) will be true
[tex]\\ \sf\longmapsto P(k)=2k^3-3k^2+k+6=6m[/tex]
- m means multiple .
We shall prove it for P(k+1)
[tex]\\ \sf\longmapsto P(k+1)[/tex]
[tex]\\ \sf\longmapsto 2(k+1)^3-3(k+1)^2+(k+1)+6[/tex]
[tex]\\ \sf\longmapsto 2(k^3+3k^2+3k+1)-3(k^2+2k+1)+k+1+6[/tex]
[tex]\\ \sf\longmapsto 2k^3+6k^2+6k+2-3k^2-6k-3+k+7[/tex]
[tex]\\ \sf\longmapsto 2k^3+6k^2-3k^2+6k-6k+k+2-3+7[/tex]
[tex]\\ \sf\longmapsto 2k^3+3k^2+k-1+7[/tex]
[tex]\\ \sf\longmapsto 2k^3+3k^2+k+6[/tex]
[tex]\\ \sf\longmapsto 2k^3-3k^2+k+6(-1)[/tex]
[tex]\\ \sf\longmapsto -mq[/tex]
Here
- q stands for any multiple of 6
Hence.
[tex]\\ \sf\longmapsto P(k+1)=-mq=[/tex]
- -mq is also a multiple of 6
Thus
- P(k+1) is also true .
Hence from the principle of mathematical induction P(n) is true for n[tex]\epsilon[/tex]N.
6 is of course a multiple of 6, so you need only focus on [tex]2n^3-3n^2+n[/tex].
When n = 1, this expression has a value of 2 - 3 + 1 = 0, which is indeed a multiple of 6 (and any natural number for that matter).
Assume that 6 divides [tex]2k^3-3k^2+k[/tex].
Now,
[tex]2(k+1)^3 - 3(k+1)^2 + (k+1) = (2k^3 + 6k^2 + 6k + 2) - (3k^2 + 6k + 3) + (k + 1) \\\\ = 2k^3 + 3k^2 + k \\\\ = 2k^3 - 3k^2 + k + 6k[/tex]
and this is divisible by 6. (6k is obviously a multiple of 6; that 6 divides the other three terms is due to the induction hypothesis.)